2003
DOI: 10.1021/bi026983p
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among the Three Structural Motifs of the C-Terminal Region of Human Thrombospondin-2

Abstract: The C-terminal regions of thrombospondins (TSPs) contain three elements, EGF-like modules (E), a series of Ca(2+)-binding repeats (Ca), and a C-terminal sequence (G). We have looked for interactions among these elements in four recombinant proteins based on human TSP-2: E3CaG-2, CaG-2, E3Ca-2, and Ca-2. When bound Ca(2+) was assayed by atomic absorption spectroscopy or an equilibrium dialysis protocol in which Ca(2+) was removed from the proteins prior to equilibrium dialysis, E3CaG-2 bound 22-27 Ca(2+), CaG-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 49 publications
8
21
1
Order By: Relevance
“…Proteins were initially treated with 4 mM EDTA to remove Ca 2ϩ and then dialyzed exhaustively at 4°C into buffer containing 5 mM MOPS and 0.1 M NaCl (pH 7.5). Ca 2ϩ -depleted protein (45 l) was then dialyzed at 37°C for 4 h into the same buffer (350 l) containing [Ca 2ϩ ] varying from 10 M to 2 mM plus trace 45 CaCl 2 (Amersham Biosciences) (21,22). Following dialysis, the radioactivity of the protein and buffer samples was determined by scintillation counting, and the protein concentration of the protein samples was determined by BCA protein assay (Pierce Intrinsic UV Fluorescence and Titration with Ca 2ϩ or Tb 3ϩ -Prior to fluorescence assays, recombinant proteins were treated with 4 mM EDTA to remove the Ca 2ϩ and then dialyzed at 4°C into buffer containing 5 mM MOPS and 0.1 M NaCl (pH 7.5), as described above.…”
Section: Cloning Of Common and Polymorphic Truncation Constructs-tomentioning
confidence: 99%
“…Proteins were initially treated with 4 mM EDTA to remove Ca 2ϩ and then dialyzed exhaustively at 4°C into buffer containing 5 mM MOPS and 0.1 M NaCl (pH 7.5). Ca 2ϩ -depleted protein (45 l) was then dialyzed at 37°C for 4 h into the same buffer (350 l) containing [Ca 2ϩ ] varying from 10 M to 2 mM plus trace 45 CaCl 2 (Amersham Biosciences) (21,22). Following dialysis, the radioactivity of the protein and buffer samples was determined by scintillation counting, and the protein concentration of the protein samples was determined by BCA protein assay (Pierce Intrinsic UV Fluorescence and Titration with Ca 2ϩ or Tb 3ϩ -Prior to fluorescence assays, recombinant proteins were treated with 4 mM EDTA to remove the Ca 2ϩ and then dialyzed at 4°C into buffer containing 5 mM MOPS and 0.1 M NaCl (pH 7.5), as described above.…”
Section: Cloning Of Common and Polymorphic Truncation Constructs-tomentioning
confidence: 99%
“…The addition of a single calcium ion in the THBS-1 construct could be due to the higher calcium concentration used for crystallization (5 mM CaCl 2 used in THBS-1 [10] versus 2 mM CaCl 2 used in THBS-2 [11]). Calcium-binding studies of THBS-1 and THBS-2 have not shown a difference in numbers of calcium bound between these proteins, but a difference of one calcium ion would fall within the experimental error [41,44].…”
Section: The Globementioning
confidence: 78%
“…Interestingly, the circular dichroic spectrum of a THBS-2 construct comprising solely its wire repeats displays a calcium-dependent ellipticity minimum at 203 nm that is characteristic of the circular dichroic spectra of all THBSs studied to date [44]. The wire-containing protein is denatured only slightly more readily than the full signature domain [44]. Thus, the wire forms a stable, calcium-dependent structure that is independent of the rest of the signature domain.…”
Section: Effects Of Calciummentioning
confidence: 99%
See 2 more Smart Citations